2006
DOI: 10.1103/physrevd.73.077503
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Lambda polarization in high energyppcollisions with polarized beams

Abstract: We study the polarization of the anti-Lambda particle in polarized high energy pp collisions at large transverse momenta. The anti-Lambda polarization is found to be sensitive to the polarization of the anti-strange sea of the nucleon. We make predictions using different parameterizations of the polarized quark distribution functions. The results show that the measurement of longitudinal antiLambda polarization can distinguish different parameterizations, and that similar measurements in the transversely polar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 56 publications
3
68
0
1
Order By: Relevance
“…[32] are shown in Fig. 7, together with our previous results for PΛ [26]. The main characteristics are:…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…[32] are shown in Fig. 7, together with our previous results for PΛ [26]. The main characteristics are:…”
Section: Resultsmentioning
confidence: 57%
“…Phenomenological studies of longitudinal hyperon polarization may be found in Refs. [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. The main themes of these studies can be categorized as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of D LL for inclusive Λ andΛ production may provide constraints on strange (anti) quark polarization [35] and can yield new insight into polarized fragmentation functions [36]. The extension of the p T region to large values is essential.…”
Section: Star Longitudinal Spin Program -Recent Resultsmentioning
confidence: 99%
“…The spin transfer to Λ andΛ hyperons has been studied extensively in a number of theoretical models [6][7][8][9][10][11][12][13][14] for e + e − collisions and lepton DIS. From a theoretical point of view the simplest case is the polarisation of the hyperons formed in e + e − annihilation at the Z-peak, where the hadronisation of the qq-system can be well described using independent fragmentation.…”
Section: Introductionmentioning
confidence: 99%